Processing And Properties Of Ni/YSZ Composite Coating On High Speed Steel Cutting Tool - Saiful Bahri, Mohamed; N. B., Baba; M. F., Omar; S., Sharif (2018)
The study involves coating the high speed steel (HSS) tool with Ni/YSZ composite via electroless nickel co-deposition. Common commercialized coated cutting tool are AlN, TiN, TiAlN and in this study Ni/YSZ is investigated. Ni/YSZ composite was successfully coated onto the HSS cutting tool via electroless nickel co-deposition. The performance of Ni/YSZ composite coated tool was compared to the uncoated and TiN coated tools for its surface tolerance in milling of mild steel. Five samples of each type of cutting tools were run by using Deckel Maho DMU50 CNC machine with five different levels of spindle speed ranges between 800-1200 rpm and five different cutting lengths between 120-600 mm. The machined work material surface tolerances were recorded using Mitutoyo SJ-301 surface roughness tester. SEM/EDX analysis confirmed the existence of Ni and YSZ in the coating.